2013
DOI: 10.1037/a0027892
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal affective decision making revealed in adolescent binge drinkers using a functional magnetic resonance imaging study.

Abstract: The goal of this study was to investigate the neural correlates of affective decision making, as measured by the Iowa Gambling Task (IGT), which are associated with adolescent binge drinking. Fourteen adolescent binge drinkers (16-18 years of age) and 14 age-matched adolescents who had never consumed alcohol--never drinkers--were recruited from local high schools in Chengdu, China. Questionnaires were used to assess academic performance, drinking experience, and urgency. Brain regions activated by the IGT perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
93
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 62 publications
(98 reference statements)
9
93
0
8
Order By: Relevance
“…Gaining a better understanding of alcohol use effects during this crucial developmental stage has been positioned in national scientific consciousness and federal funding initiatives over the past two decades (Brown et al, 2008;Windle et al, 2008). Cross-sectional studies have identified brain structural and functional abnormalities (Cservenka et al, 2014;De Bellis et al, 2005McQueeny et al, 2009;Nagel et al, 2005;Petit et al, 2014;Schweinsburg et al, 2010;Tapert et al, 2004), neurocognitive deficits (Brown et al, 2000;Silveri, 2014;Whelan et al, 2014;Xiao et al, 2013), and poorer psychosocial functioning (Anderson et al, 2010;Brown et al, 2008;Fergusson & Lynskey, 1996;Zucker et al, 2008) in heavydrinking adolescents relative to non-/low (NON) drinking counterparts. Deleterious effects of alcohol consumption have been associated with heavy drinking episodes (Chassin et al, 2002;McQueeny et al, 2009), defined as consuming four or more drinks on a single occasion for females and five or more drinks for males (National Institute on Alcohol Abuse and Alcoholism [NIAAA], 2004;Wechsler et al, 1995).…”
mentioning
confidence: 99%
“…Gaining a better understanding of alcohol use effects during this crucial developmental stage has been positioned in national scientific consciousness and federal funding initiatives over the past two decades (Brown et al, 2008;Windle et al, 2008). Cross-sectional studies have identified brain structural and functional abnormalities (Cservenka et al, 2014;De Bellis et al, 2005McQueeny et al, 2009;Nagel et al, 2005;Petit et al, 2014;Schweinsburg et al, 2010;Tapert et al, 2004), neurocognitive deficits (Brown et al, 2000;Silveri, 2014;Whelan et al, 2014;Xiao et al, 2013), and poorer psychosocial functioning (Anderson et al, 2010;Brown et al, 2008;Fergusson & Lynskey, 1996;Zucker et al, 2008) in heavydrinking adolescents relative to non-/low (NON) drinking counterparts. Deleterious effects of alcohol consumption have been associated with heavy drinking episodes (Chassin et al, 2002;McQueeny et al, 2009), defined as consuming four or more drinks on a single occasion for females and five or more drinks for males (National Institute on Alcohol Abuse and Alcoholism [NIAAA], 2004;Wechsler et al, 1995).…”
mentioning
confidence: 99%
“…En estudios locales previos tampoco se reportaron diferencias en función del sexo cuando se consideraron las puntuaciones de esa prueba (Bosch et al, 2016). Por otro lado, en relación al PCA de los participantes, los estudios que reportan diferencias en el rendimiento en la IGT son aquellos que compararon participantes abstemios con bebedores, principalmente bebedores intensivos (Johnson et al, 2008;Xiao et al, 2013). En estudios locales, por otro lado, solo se compararon bebedores con distinto PCA, sin un grupo de abstemios.…”
Section: Cuestionario De Impulsividad Upps-p (Whiteside Yunclassified
“…Al respecto, algunos estudios señalan que individuos con problemas en su capacidad de TD, la mayoría de las veces, no pueden resistirse al acceso a las sustancias de abuso disponibles en su entorno (Bechara, 2005;Goldstein & Volkow, 2002). De esta manera, es posible que los adolescentes y jóvenes con un consumo de alcohol que en principio es casual y no problemático avancen hacia un consumo compulsivo y descontrolado (Xiao et al, 2013 (Crews, He, & Hodge, 2007;Mota et al, 2013;Parada et al, 2012).…”
unclassified
“…The reward system is also impacted by the hormones associated with puberty, indicating a link between decision-making abilities and puberty. Variation between individual development of decisionmaking skills and between the genders has been demonstrated (Xiao et al, 2012;. This study can help determine if self-management skills are likely to be linked or needed for profiles of high decision-making skills around the time of puberty.…”
Section: The Heterogeneity Of Sel Skills; Relation To Puberty and Funmentioning
confidence: 99%
“…Relationship skills in adolescence are predictive of positive adjustment (Laible, Carlo, & Raffaelli, 2000) and poor relationship skills are linked to social exclusion, which has long lasting and detrimental effects . Decision-making during adolescence is studied extensively, as adolescents are given more autonomy on making their own decisions and are known for making risky decisions (Wray-Lake, Crouter, & McHale, 2011;Xiao et al, 2012).…”
mentioning
confidence: 99%